Religion and Violence in the Horn of Africa: Trajectories of Mimetic Rivalry and Escalation between ‘Political Islam’ and the State - Abbink, Jon (Politics, religion & ideology, 2020)
Religiously inspired violence is a global phenomenon and connects to transnational narratives, necessitating comparative analysis of socio-historical context and patterns of ideological mobilization. Northeast Africa hosts several radical-extremist and terrorist groups, mostly of Muslim persuasion, tuned in to these global narratives while connecting to local interests. Christian radicalism and violence also occur but are less ideologically consistent and less widespread. I examine key aspects of the current role and ideological self-positioning of Islamist radicalism in state contexts, comparing Somalia, affected by Islamist violence since the late 1990s, and Ethiopia, where Islam's mobilization followed a different path and where the state so far contained politicization and open radicalism of Muslim groups. A brief contrastive case from Nigeria is also provided. It is observed that Islam, while of course not ‘equaling’ violence, easily provides a militant political theology, frequently instrumentalized in conflicts and situations of (perceived) grievance, and via mimetic rivalry then becomes radically ideological. Securitized response patterns of state authorities toward militancy play a role in furthering violent radicalization. I follow a sociological-anthropological approach but also refer to key aspects of national-legal frameworks regarding state and religion, next to societal and political bases of Muslim militant mobilization for collective aims and self-presentation.